Clinical usefulness of single-balloon endoscopy in patients with previously incomplete colonoscopy - Kobayashi, Kiyonori (Baishideng Publishing Group Co., Limited, 2013)
AIM: To evaluate the clinical usefulness of single-balloon endoscopy (SBE) in patients in whom a colonoscope was technically difficult to insert previously. METHODS: The study group comprised 15 patients (8 men and 7 women) who underwent SBE for colonoscopy (30 sessions). The number of SBE sessions was 1 in 7 patients, 2 in 5 patients, 3 in 1 patient, 4 in 1 patient, and 6 in 1 patient. In all patients, total colonoscopy was previously unsuccessful. The reasons for difficulty in scope passage were an elongated colon in 6 patients, severe intestinal adhesions after open surgery in 4, an elongated colon and severe intestinal adhesions in 2, a left inguinal hernia in 2, and multiple diverticulosis of the sigmoid colon in 1. Three endoscopists were responsible for SBE. The technique for inserting SBE in the colon was basically similar to that in the small intestine. The effectiveness of SBE was assessed on the basis of the success rate of total colonoscopy and the presence or absence of complications. We also evaluated the diagnostic and treatment outcomes of colonoscopic examinations with SBE. RESULTS: Total colonoscopy was successfully accomplished in all sessions. The mean insertion time to the cecum was 22.9 ± 8.9 min (range 9 to 40). Abnormalities were found during 21 sessions of SBE. The most common abnormality was colorectal polyps (20 sessions), followed by radiation colitis (3 sessions) and diverticular disease of the colon (3 sessions). Colorectal polyps were resected endoscopically in 15 sessions. A total of 42 polyps were resected endoscopically, using snare polypectomy in 32 lesions, hot biopsy in 7 lesions, and endoscopic mucosal resection in 3 lesions. Fifty-six colorectal polyps were newly diagnosed on colonoscopic examination with SBE. Histopathologically, these lesions included 2 intramucosal cancers, 42 tubular adenomas, and 2 tubulovillous adenomas. The mean examination time was 48.2 ± 20.0 min (range 25 to 90). Colonoscopic examination or endoscopic treatment with SBE was not associated with any serious complications. CONCLUSION: SBE is a useful and safe procedure in patients in whom a colonoscope is technically difficult to insert.